Are Organizational Commitment and Compensation Predicting Employeeâs Performance? - Tentama, Fatwa (Universitas Ahmad Dahlan, 2015)
AbstractThe problem, which an organization often faces, is the employeesâ performance, which Â results in ineffective organization. Commitment and compensation are factors affecting theÂ employeesâ performance. This research aims at empirically examining the role of commitment Â and compensation of employeesâ performance. The subjects of the research are permanentÂ employees at Ahmad Dahlan University, having served for more than one year.Â The sampling technique is non-randomized. The method of collecting data uses commitment,compensation, and performance scales. The data are analyzed with multiple linear regressionÂ technique. The result shows that the organizational commitment and the compensationÂ simultaneously predict the employeesâ performance of (r)= 0,594 and the significanceÂ correlation coefficient of F reg. = 12.815 with p = 0,000 (p<0,01), which means there is aÂ very significant positive correlation among organizational commitment and compensationsimultaneously with the performance of the employees of Ahmad Dahlan University. TheÂ implication of study is discussed further in article.Keywords: organizational commitment, compensation, performance